The Amsterdam Studies of Acute Psychiatry - II (ASAP-II): a comparative study of psychiatric intensive care units in the Netherlands - van Venrooij Janine; van Egmond Marieke; Klaassen André; Barkhof Emile; Hornbach Annett; Mulder Wijnand; van Wijk Cecile; Schoevers Robert; Koppelmans Vincent; Bijpost Yan; Nusselder Hans; van Herrewaarden Marjan; et al. (BMC, 2009)
Abstract Background The number of patients in whom mental illness progresses to stages in which acute, and often forced treatment is warranted, is on the increase across Europe. As a consequence, more patients are involuntarily admitted to Psychiatric Intensive Care Units (PICU). From several studies and reports it has become evident that important dissimilarities exist between PICU's. The current study seeks to describe organisational as well as clinical and patient related factors across ten PICU's in and outside the Amsterdam region, adjusted for or stratified by level of urbanization. Method/Design This paper describes the design of the Amsterdam Studies of Acute Psychiatry II (ASAP-II). This study is a prospective observational cohort study comparing PICU's in and outside the Amsterdam region on various patient characteristics, treatment aspects and recovery related variables. Dissimilarities were measured by means of collecting standardized forms which were filled out in the framework of care as usual, by means of questionnaires filled out by mental health care professionals and by means of extracting data from patient files for every consecutive patient admitted at participating PICU's during a specific time period. Urbanization levels for every PICU were calculated conform procedures as proposed by the Dutch Central Bureau for Statistics (CBS). Discussion The current study may provide a deeper understanding of the differences between psychiatric intensive care units that can be used to promote best practice and benchmarking procedures, and thus improve the standard of care.